DESIGN AND REALIZATION OF A 700-1400 MHZ STEPPED FREQUENCY CONTINUOUS WAVE GROUND PENETRATING RADAR (SFCW-GPR) TRANSCEIVER - HARIYADI (NIM: 23207021), TOMMI
The objective of this research is to develop a SFCW-GPR transceiver that can detect a target in the soil or sand as well as behind concrete wall. Prior to the realization, first of all is simulation in a level system using SystemVueTM and MATLAB®. The simulation is based on block diagram and specification which have been determined regarding to the availability of components on the market. The result that can be obtain from simulation is that SFCW-GPR has 9.5 cm of resolution and unambiguous range 6.08 m. The influence of harmonics frequency to the signal reconstruction result and the maximum distance of target which still can be detected with the availability of link budget will be demonstrated in the simulation. Based on measurement in the laboratory both subsystem and overall system, transceiver meets the specifications have been determined. Calibration should be done before the system will be used for sensing a target that is to check the linearity of phase. This SFCW-GPR system can detect the presence of a target behind a concrete wall based on the result of laboratory measurement.